SYSTEMATIC REVISION OF INTERATHERIUM AND ICOCHILUS (INTERATHERIIDAE, NOTOUNGULATA) FROM THE SANTA CRUZ FORMATION (EARLY TO MIDDLE MIOCENE), SANTA CRUZ PROVINCE, ARGENTINA (Ameghiniana, 2023)
Interatheriidae (late Paleocene–Late Miocene) is one of the most morphologically derived families within Order Notoungulata and the most taxonomic diverse and abundant clade of extinct South American Native Ungulates. Most of the interatheriids described during late 19th century were erected from specimens collected from the prolific Santa Cruz Formation (Santacrucian SALMA; Burdigalian–early Langhian), Santa Cruz Province (Argentina). Interatherium, the type genus of the family, and Icochilus, a closely related genus, were last revised more than a century ago, and most species were considered Typotheria incertae sedis. This contribution provides the taxonomic revision of these genera, made within the framework of an exhaustive unpublished systematic revision of Interatheriinae. We propose several synonyms, including the synonymy between both genera. We conclude that Interatherium is comprised of I. rodens and I. extensus, and consider Interatherium supernum as nomen nudum according to its first description in 1887, and Interatherium brevifrons and Icochilus curtus as species inquirenda. This taxonomic scheme is supported by a phylogenetic analysis, in which Interatherium is recovered as a monophyletic genus and as the sister taxon of the clade Neoicochilus plus Cochilius. In a biostratigraphic context, it is not possible to subdivide the Santa Cruz Formation based on the presence/absence of any species of Interatherium, due to their wide geographic and temporal distribution. Finally, the localities from the Atlantic coast (east) and Río Santa Cruz (central) are similar in their content concerning Interatherium, but both differ from that of the western area, which lacks any evidence of this genus.